Digital heritage interpretation: a conceptual framework. Issue 2 (3rd July 2018) - Rahaman, Hafizur
ABSTRACT: 'Heritage Interpretation' has always been considered as an effective learning, communication and management tool that increases visitors' awareness of and empathy to heritage sites or artefacts. Yet the definition of 'digital heritage interpretation' is still wide and so far, no significant method and objective are evident within the domain of 'digital heritage' theory and discourse. Considering 'digital heritage interpretation' as a process rather than as a tool to present or communicate with end-users, this paper presents a critical application of a theoretical construct ascertained from multiple disciplines and explicates four objectives for a comprehensive interpretive process. A conceptual model is proposed and further developed into a conceptual framework with fifteen considerations. This framework is then implemented and tested on an online platform to assess its impact on end-users' interpretation level. We believe the presented interpretive framework (PrEDiC) will help heritage professionals and media designers to develop interpretive heritage project.